Exploring potential application of novel urease-producing bacterium for sustainable soil stabilization via microbially induced calcium carbonate precipitation - Jayakrishnan, Achuth; Kozhipally, Abhijith; Ramasamy, Mahenthiran (Acta Scientiarum. Biological Sciences, 2025)
Microbially induced calcium carbonate precipitation (MICP) is a sustainable process involving microbial-mediated calcium carbonate precipitation with applications in geotechnical engineering, construction, and environmental remediation. Soil samples from paddy fields were screened for ureolytic bacteria, and the isolate with the highest urease activity was identified as Bacillus tequilensis strain AK1 via 16S rRNA sequencing. The strain achieved a maximum CaCO₃ precipitation of 23.00 mg mL-1 on Day 20 in broth media and a calcite precipitation zone diameter of 17.05 mm in agar media. Bioconsolidation of soil with Bacillus tequilensis strain AK1 showed significant enhancements in soil properties. Retention time increased to 164 sec compared to 15 sec in controls, while penetration distance decreased to 43 mm, a substantial reduction from 483 mm in untreated samples. Water absorption was notably reduced to 7.4%, compared to 66.5% in controls. These findings confirm that microbial calcite precipitation effectively aggregates particles and fills pore spaces, improving soil structural integrity. This study highlights the potential of Bacillus tequilensis strain AK1 for sustainable bioconsolidation, offering a promising solution for soil stabilization, construction, and environmental remediation.